2018
DOI: 10.1002/suco.201700278
|View full text |Cite
|
Sign up to set email alerts
|

Elevated slabs made of hybrid reinforced concrete: Proposal of a new design approach in flexure

Abstract: When designing fiber-reinforced concrete (FRC) structures, one of the basic design issues is represented by the choice of a proper combination of fibers and conventional reinforcement that allows to obtain the best structural performance with the minimum amount of materials. The combination of rebars and fibers in the concrete matrix is generally known as Hybrid Reinforced Concrete (HRC). HRC represents a feasible solution in many structures; among these, slabs are gaining an increasing interest among practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…• ductility requirements often impose the presence of conventional reinforcement, especially in linear [40] elements but also in elevated slabs; rebars may take additional stresses due to FRC creep that are negligible in most cases. • When FRC is adopted for substituting secondary reinforcement for stress redistribution, creep has a minor influence since FRC is not necessary for equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• ductility requirements often impose the presence of conventional reinforcement, especially in linear [40] elements but also in elevated slabs; rebars may take additional stresses due to FRC creep that are negligible in most cases. • When FRC is adopted for substituting secondary reinforcement for stress redistribution, creep has a minor influence since FRC is not necessary for equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Other cases that are of increasing interest in recent years are elevated two-ways slabs [39,40], due to the smaller reinforcement ratio needed. Here fibers can substitute most of the traditional reinforcement and, due to the high degree of redundancy, these structures allow a significant stress redistribution.…”
Section: Shear In Linear Elements With Rebars As Bending Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, field applications of UHPC are still limited since the preparation of UHPC normally requires high fiber volume fraction (≥2%) and fine powders, which leads to complexity in preparation, construction and high costs 8 . In addition, if steel fibers are used as the sole or primary reinforcement, significantly increased fiber dosage will be required in the whole structure to resist high stresses acting only in localized areas 5 . As a result, hybrid reinforced UHPC containing steel bars and fibers are being studied and applied to obtain efficient structural performance with reduced fiber contents.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of the tensile behavior of concrete due to the use of fibers can be exploited to enhance the ultimate and the serviceability performance of different kinds of structures [19]. Several research studies have proven the ability of fibers to partially or even totally replace conventional steel reinforcement in structures characterized by a significantly high degree of redundancy, such as slab-on-grade and elevated slabs [20]. Other authors have shown the possibility of partially replacing either the flexural or the shear reinforcement in concrete beams [21].…”
Section: Introductionmentioning
confidence: 99%